MANAJEMEN HUBUNGAN MASYARAKAT DALAM PENINGKATAN LAYANAN PESANTREN AL-YUSUFIYAH HUTA HOLBUNG TAPANULI SELATAN - Salim Salim (Jurnal Al-Fatih, 2022)
The formulation of the research problem is how to manage public relations in improving pesantren services. While the objectives of this study are: (1) how to plan community relations in improving pesantren services, (2) how to implement public relations programs in improving Islamic boarding schools services, and (3) how to evaluate public relations programs in improving pesantren services. The method of this research is qualitative data collection using interviews, observation and documentation. The data analysis technique used is the process of data reduction, data presentation, and drawing conclusions/verification. To ensure the validity of the data, in this case cross-checking or triangulation of data obtained by interviews, observation and documentation is carried out. In addition, cross-checking was carried out by cross-checking between informants, data from pesantren foundations, checking with data from madrasa leaders and heads. Likewise, data from leadership staff was checked for correctness by checking data from teachers, and education staff at the Al Yusufiyah Huta Holbung Islamic boarding school so that the data was completely saturated or there was no variation in the data obtained. There are three findings in this study, namely: 1. Planning for community relations in improving services is carried out by means of deliberation of all elements of the pesantren, both pesantren foundations, pesantren leaders, madrasa heads, staff and teachers at work meetings every year. In the work deliberation of the Al Yusufiyah pesantren, a public relations work program was produced as a guide for pesantren activities every year as a result of joint formulation in the field of disseminating external information to the government, community, and all pesantren stakeholders.2. The implementation of the public relations program in improving the services of the Al Yusufiyah Huta Holbung pesantren in Batang Angkola sub-district includes curriculum and learning development, new student admissions and orientation, teaching and learning activities, and evaluation of student teaching and learning activities. The implementation of the public relations program in this field is carried out through sending information and external communication using brochures and pamphlets, posters, bulletins, audio, and audiovisual as well as videos, disseminating information via the web, using YouTube, about the Yusufiyah Islamic Boarding School through https://yotoube.com or http: //www.tower today.com. according to public relations programs in improving services as an external communication pesantren.3. Evaluation of Public Relations in improving the academic services of the Yusufiyah pesantren is carried out through a written report on the implementation of the public relations program given to the Yusufiyah pesantren foundation, every semester. In the elements of the report, the name of the activity, objectives, implementation of the activity, obstacles/problems encountered and alternative solutions selected in solving the problems encountered are reported.